Training Experience in ICT from a Gender Perspective - Del Prete, Annachiara (2013)
This article is based on the project: “ICT as a tool of empowerment for the group of older women”,that has consisted of a series of workshops on basic computer skills targeted to a group of womenwhose ages are between 50 and 70 years, of the Municipality of Pamplona (Norte de SantanderColombia). By using a qualitative methodological paradigm we intended to train older womenparticipating in the project of using ICT as a tool of empowerment and knowledge constructionthrough the recovery of memory. The results have been a significant change of discourse regardingthe self-concept of them and editing a document in digital and paper format that recompiles andsaves the history of women in the municipality and its participation in economic and culturaldevelopment of the municipality.